Portfolio performance under tracking error and benchmark volatility constraints - Hausner, Jan Frederick; van Vuuren, Gary (Universidad ESAN. ESAN Ediciones, 2021)
Purpose. Using a portfolio comprising liquid global stocks and bonds, this study aims to limit absolute risk to that of a standardised benchmark and determine whether this has a significant impact on expected return in both high volatility period (HV) and low volatility period (LV). Design/methodology/approach. Using a traditional benchmark comprising 40% equity and 60% bonds, a constant tracking error (TE) frontier was constructed and implemented. Portfolio performance for different TE constraints and different economic periods (expansion and contraction) was explored. Findings. Results indicate that during HV, replicating benchmark portfolio risk produces portfolios that outperform both the maximum return (MR) portfolio and the benchmark. MR portfolios outperform those with the same risk as that of the benchmark in LV. The MR portfolio weights assets to obtain the highest return on the TE frontier. During HV, the benchmark replicated risk portfolio obtained a higher absolute risk value than that of the MR portfolio because of an inefficient benchmark. In HV, the benchmark replicated risk portfolio favoured intermediate maturity treasury bills. Originality/value. There is a dearth of literature exploring the performance of active portfolios subject to TE constraints. This work addresses this gap and demonstrates, for the first time, the relative portfolio performance of several standard portfolio choices on the frontier.

Propósito: Utilizando una cartera que comprende acciones y bonos globales líquidos, este estudio tiene como objetivo limitar el riesgo absoluto al de un índice de referencia estandarizado y determinar si esto tiene un impacto significativo en el rendimiento esperado tanto en el período de alta volatilidad (HV) como en el período de baja volatilidad (LV). Diseño/metodología/enfoque: Utilizando un punto de referencia tradicional compuesto por 40% de acciones y 60% de bonos, se construyó e implementó una frontera de error de seguimiento constante (TE). Se exploró el desempeño de la cartera para diferentes restricciones de TE y diferentes períodos económicos (expansión y contracción). Hallazgos: Los resultados indican que durante HV, la replicación del riesgo de la cartera de referencia produce carteras que superan tanto a la cartera de rendimiento máximo (MR) como a la de referencia. Las carteras MR superan a aquellas con el mismo riesgo que el índice de referencia en LV. La cartera MR pondera los activos para obtener el mayor rendimiento en la frontera TE. Durante HV, la cartera de riesgo replicado de referencia obtuvo un valor de riesgo absoluto más alto que el de la cartera de MR debido a una referencia ineficiente. En HV, la cartera de riesgo replicado de referencia favoreció las letras del Tesoro de vencimiento intermedio. Originalidad/valor: Hay escasez de literatura que explore el desempeño de carteras activas sujetas a restricciones de TE. Este trabajo aborda esta brecha y demuestra, por primera vez, el desempeño relativo de varias opciones de cartera estándar en la frontera.
Keywords: Tracking error; Portfolio performance optimisation; Error de seguimiento; Optimización del rendimiento de la cartera; Active management; Gestión activa; https://purl.org/pe-repo/ocde/ford#5.02.04